Performance Analysis of TCP Fractional Window Increment and Adaptive Fractional Window on IEEE 802.11 Multihop Ad Hoc Networks - Hilal Hudan Nuha; Vera Suryani; Arnas Sofyan (International Journal on Information and Communication Technology (IJoICT), 2023)
TCP, a layer 4 transport protocol, plays a crucial role in both wireless and wired networks. However, its performance in wireless networks is often unsatisfactory due to issues such as bandwidth limitations and utility problems with lower network layers. The mobility effect further exacerbates TCP's performance, as it fails to distinguish between connection failure and congestion-induced connection loss. In response to this challenge, researchers have explored potential solutions and found that TCP FeW outperforms the existing TCP NewReno. Building upon this background, this paper aims to simulate and analyze the performance of TCP AFW and TCP FeW in an IEEE 802.11 network. The simulations conducted using ns2 in a limited environment with random mobile scenarios reveal that TCP AFW achieves a 1.12% higher throughput compared to FeW, even with minimal modifications.